Bank Nationalization and its Reforms in India - Vaish, Dr. P.C. (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Capital is the vitality of the modern economy. Capital has traditionally been money saved and lent. But in modern banks that use partial preliminary loans, banks can digitally generate capital. Increasing the availability of capital helps economic growth, but can be miserable if not properly managed. Economist Hyman Minsky blamed excessive debt for most of the financial crisis. He identified three types of debt. The safest debt he calls "hedge financing" is responsible for economic growth. The borrower invests capital in productive economic activities where cash flows can serve interest and eventually pay off the principal. Risky debt called 'financial financing' includes credit for marginal businesses that are forced by the government through priority loan schemes, where current cash flows are sufficient to pay interest and later roll over the principal. Date. Sometimes it works, but the economic downturn exacerbates the risk of default. The third debt, which Minsky calls 'Ponzi financing', was the most dangerous because the borrower would not use capital to invest in production activities, but would repay the debt at a higher price, pay off the debt, and buy the assets that expect profits. This paper briefly analyzes India's bank nationalization and its reforms. Keywords: Bank nationalization, non-performance assets, financial crisis